Вплив кольору на сприйняття бренду - Цвігун, А. О. (ХНУРЕ, 2023)
The effect of color on brand perception is a topic that explores the impact of color on brand perception and its effectiveness in marketing strategy. The color palette is determined based on the characteristics of the brand and the target audience. Studies indicate that colors can evoke certain emotions and associations in consumers, so using colors correctly in marketing campaigns and brand design is important. For example, the color red can evoke associations with energy and power, while blue is associated with calmness and trust. The results of the studies can help marketers and designers choose a color palette that is appropriate for a specific brand and ensure its success in the market
Keywords: бренд; колір